"Why Do Kids Quit?" survey - Tuffey, S.; Medbery, R.; Gould, D.
Two years ago, USA Swimming undertook an investigation in an attempt to understand why kids quit swimming as it was reported that about 35% (60,000) of age group swimmers drop out of the sport each year. Results of this study revealed that fun was a major factor contributing to athlete motivation to swim (Tuffey, 1996). Kids reported continuing their involvement in swimming because it was fun and discontinuing their involvement in swimming because it was no longer fun. In fact, fun/enjoyment was identified as the number one reason why kids swim. Unfortunately, the study was not designed to determine what specifically was and was not fun for age group swimmers. Because of an expressed interest from USA Swimming coaches, a follow-up study was designed and conducted to identify specific factors that make swimming fun and specific factors that detract from fun for age group swimmers. Additionally, we were interested in assessing whether any age, gender, or ability-related differences exist in sources of fun in swimming as this would be valuable information for coaches.